2023
DOI: 10.1371/journal.pgen.1010849
|View full text |Cite
|
Sign up to set email alerts
|

A Van Gogh/Vangl tyrosine phosphorylation switch regulates its interaction with core Planar Cell Polarity factors Prickle and Dishevelled

Abstract: Epithelial tissues can be polarized along two axes: in addition to apical-basal polarity they are often also polarized within the plane of the epithelium, known as planar cell polarity (PCP). PCP depends upon the conserved Wnt/Frizzled (Fz) signaling factors, including Fz itself and Van Gogh (Vang/Vangl in mammals). Here, taking advantage of the complementary features of Drosophila wing and mouse skin PCP establishment, we dissect how Vang/Vangl phosphorylation on a specific conserved tyrosine residue affects … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…There are at least three possibilities accounting for how Pk can assist Vangl2 to sequester Dvl. First, given that Dvl, Pk and Vang/Vangl can mutually interact with each other (Bastock et al, 2003; Humphries et al, 2023; Jenny et al, 2003; Takeuchi et al, 2003; Tree et al, 2002), Pk may stabilize a ternary Dvl/Pk/Vangl complex by simultaneously interacting with both Vangl and Dvl (Fig. 9a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are at least three possibilities accounting for how Pk can assist Vangl2 to sequester Dvl. First, given that Dvl, Pk and Vang/Vangl can mutually interact with each other (Bastock et al, 2003; Humphries et al, 2023; Jenny et al, 2003; Takeuchi et al, 2003; Tree et al, 2002), Pk may stabilize a ternary Dvl/Pk/Vangl complex by simultaneously interacting with both Vangl and Dvl (Fig. 9a).…”
Section: Discussionmentioning
confidence: 99%
“…We, however, do not favor this possibility because 1) the binding between Pk and Dvl was reported to be quite weak (Bastock et al, 2003); 2) our unpublished data show that ΔPL, a Pk mutant lacking the PET/LIM domains necessary for Dvl binding (Takeuchi et al, 2003), can largely mimic wild-type Pk function. Furthermore, a new study in flies showed that the phosphorylation status of a conserved tyrosine in the cytoplasmic tail of Vang provides opposite binding preference for Pk and Dsh, suggesting that simultaneous binding of both Pk and Dsh to the C-terminus of Vang may not be possible (Humphries et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations